GASTRIC ADENOCARCINOMA DIAGNOSE : A CASE REPORT - Komang Arjawa, Ida Bagus (E-Jurnal Medika Udayana; vol 3 no 3 (2014):e-jurnal medika udayana, 2014)
Gastric cancer have become cancer number fourth from all incident of cancer and become the second killer cancer from all cancer. Undifined risk factor dan unspecific sign and symptom make most of this disease diagnosed in late phase. In this case report, a woman, 47 years old, single with main complaint nausea, vomitting and lose weight from six months ago. Diagnosed with gastric adenocarcinoma suspect IIIB stage. Diagnosing gastric cancer need completed and careful anamnesis and physical exmination. Laboratory and other examination become main modality because a long time of asymptomatic phase. Nowadays, endoscopy believed as a diagnostic methods with high sensitivity and specificity in gastric adenocarcinoma followed by CT Scan to detect metastatic process to liver and lymph node. Finaly, histology study in laboratoriu have become a gold standar to diagnose type of the neoplasm
Keywords: cancer, gastric, endoscopy